2014
DOI: 10.1097/hnp.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Peer-Led Support Groups Among Caregivers of Persons With Parkinson's Disease

Abstract: Many persons with Parkinson's disease are cared for by family members. The strain of caregiving can negatively affect the health of the caregiver and affect long-term care decisions, making caregiver support a priority. This study highlights the importance of peer-led support groups for family caregivers of persons with Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 5 publications
2
14
0
4
Order By: Relevance
“…Quanto à caracterização sociodemográfica, dos 20 familiares cuidadores que participaram do estudo, 16 eram do sexo feminino -o que não é um achado incomum, visto que a prevalência da DP é principalmente na população masculina, associado ao perfil cultural de cuidadoras mulheres (Abendroth et al, 2012;Abendroth, Greenblum, & Gray 2014;).…”
Section: Caracterização Dos Participantesunclassified
See 2 more Smart Citations
“…Quanto à caracterização sociodemográfica, dos 20 familiares cuidadores que participaram do estudo, 16 eram do sexo feminino -o que não é um achado incomum, visto que a prevalência da DP é principalmente na população masculina, associado ao perfil cultural de cuidadoras mulheres (Abendroth et al, 2012;Abendroth, Greenblum, & Gray 2014;).…”
Section: Caracterização Dos Participantesunclassified
“…Todos referiram seguir uma religião, sendo a católica a mais citada entre os participantes. Características semelhantes foram encontradas em outros estudos com familiares de pessoas com DP, sendo considerados fatores que interferem na adaptação e aceitação da doença (Abendroth et al, 2014;Peternella & Marcon, 2009;Tan et al, 2012).…”
Section: Caracterização Dos Participantesunclassified
See 1 more Smart Citation
“…Although family members have been assuming caregiving responsibilities for such individuals, many may lack the ability to accomplish such tasks in ways that preserve their own well-being. Addressing the needs of informal caregivers through various sources of informal and formal support is essential to mitigate strain and maintain home placement of persons with Parkinson's disease (Abendroth, Greenblum, & Gray, 2014;Abendroth et al, 2012).…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Russell (2004) and Eriksson et al’s (2008) work perpetuates Kaye and Crittenden’s statement, as they found that their male caregiver participants would meet with peers as a break from caregiving, and/or opportunity to seek advice and solutions to problems in the care process. Seeking peer support is not unique to men, as this support type has also been perceived as beneficial by a mostly female caregiver sample (Abendroth, Greenblum, & Gray, 2014). …”
Section: The “Male Approach” To Caregivingmentioning
confidence: 99%